β-Cyclodextrin- and adamantyl-substituted poly(acrylate) self-assembling aqueous networks designed for controlled complexation and release of small molecules - Yan, Liang; Pham, Duc-Truc; Clements, Philip; Lincoln, Stephen F.; Wang, Jie; Guo, Xuhong; Easton, Christopher J. (Beilstein Journal of Organic Chemistry, 2017)
Three aqueous self-assembling poly(acrylate) networks have been designed to gain insight into the factors controlling the complexation and release of small molecules within them. These networks are formed between 8.8% 6A-(2-aminoethyl)amino-6A-deoxy-6A-β-cyclodextrin, β-CDen, randomly substituted poly(acrylate), PAAβ-CDen, and one of the 3.3% 1-(2-aminoethyl)amidoadamantyl, ADen, 3.0% 1-(6-aminohexyl)amidoadamantyl, ADhn, or 2.9% 1-(12-aminododecyl)amidoadamantyl, ADddn, randomly substituted poly(acrylate)s, PAAADen, PAAADhn and PAAADddn, respectively, such that the ratio of β-CDen to adamantyl substituents is ca. 3:1. The variation of the characteristics of the complexation of the dyes methyl red, methyl orange and ethyl orange in these three networks and by β-cyclodextrin, β-CD, and PAAβ-CDen alone provides insight into the factors affecting dye complexation. The rates of release of the dyes through a dialysis membrane from the three aqueous networks show a high dependence on host–guest complexation between the β-CDen substituents and the dyes as well as the structure and the viscosity of the network as shown by ITC, 1H NMR and UV–vis spectroscopy, and rheological studies. Such networks potentially form a basis for the design of controlled drug release systems.
Keywords: controlled release; cyclodextrin; network; poly(acrylate); self-assembly